2022
DOI: 10.3390/ijms23020758
|View full text |Cite
|
Sign up to set email alerts
|

Repellency Mechanism of Natural Guar Gum-Based Film Incorporated with Citral against Brown Planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae)

Abstract: Using of plant essential oil that coevolved as a defense mechanism against agriculture insects is an alternative means of controlling many insect pests. In order to repel brown planthoppers (BPHs), the most notorious rice insect pest, a new film based on guar gum incorporated with citral (GC film) was formulated, which was effective while being environmentally friendly. In this paper, the effect and mechanism of GC film repellency against BPHs were determined. Repellent activity test and olfactory reaction ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Based on this, we speculated that nano-controlled release pesticide carriers, based on polysaccharides and their derivatives, could be developed simultaneously from the direction of regulating the resistance of plants themselves to pests and directly inhibiting pests (Figure 2). From the direction of regulating the resistance of plants themselves to pests, such as stimulating plant growth [31,[70][71][72][73], triggering an early warning of plant immune mechanism [53,74]. From the direction of direct inhibiting pests, the first development direction is the specific release of pesticides, which is based on the location of pests and diseases and the period of harm, such as targeting specific enzymes' environments in harmful organisms [9,33], or targeting specific pH [9,15,24,27,29,32,[34][35][36][52][53][54][55] or temperature [23,24,27,51,53,56] environments, while protecting other species, such as bees, and earthworms have a poor release capacity in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, we speculated that nano-controlled release pesticide carriers, based on polysaccharides and their derivatives, could be developed simultaneously from the direction of regulating the resistance of plants themselves to pests and directly inhibiting pests (Figure 2). From the direction of regulating the resistance of plants themselves to pests, such as stimulating plant growth [31,[70][71][72][73], triggering an early warning of plant immune mechanism [53,74]. From the direction of direct inhibiting pests, the first development direction is the specific release of pesticides, which is based on the location of pests and diseases and the period of harm, such as targeting specific enzymes' environments in harmful organisms [9,33], or targeting specific pH [9,15,24,27,29,32,[34][35][36][52][53][54][55] or temperature [23,24,27,51,53,56] environments, while protecting other species, such as bees, and earthworms have a poor release capacity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Guar gum and diquat prepared into a gel (Hydrogel) could significantly reduce the drift of off-site herbicides [69]. In addition, guar gum could also be made into a film (GC film) with related repellents, which was both effective and environmentally friendly and could slowly release the brown planthopper repellent citral [70].…”
Section: Research Progress Of Other Polysaccharide Materials and Thei...mentioning
confidence: 99%
“…Transcriptomics represents another highly efficient approach currently employed for the search of prospective biotechnology-relevant markers to establish new cultivars with high gum contents [107][108][109]. Thus, post-genomic studies combining transcriptomics and metabolomics platforms emerged over the last decade.…”
Section: The Role Of Transcriptomics Data In Breeding Of New Drought-...mentioning
confidence: 99%
“…The transcript of both HoblOBP9 and HoblOBP13 in Holotrichia oblita was significantly increased upon exposure to the attractant ( E )-2-hexenol for 24 h, while the transcript of DcitOBP7 was significantly decreased after Asian citrus psyllid Diaphorina citri was exposed to linalool for 5 h . When the brown planthopper (BPH) Nilaparvata lugens (Stål) were fed on the rice plant sprayed with a natural Guar gum-based film, which was incorporated with citral, an effective repellent for BPHs, RNA sequencing analysis showed that the relative mRNA level of an OBP coding gene named 797 was significantly decreased . Compared with the naive control, the transcriptional level of some OBPs and CSPs of M.…”
Section: Introductionmentioning
confidence: 99%
“…The transcript of both HoblOBP9 and HoblOBP13 in Holotrichia oblita was significantly increased upon exposure to the attractant (E)-2-hexenol for 24 h, 21 while the transcript of DcitOBP7 was significantly decreased after Asian citrus psyllid Diaphorina citri was exposed to linalool for 5 h. 22 When the brown planthopper (BPH) Nilaparvata lugens (Stal) were fed on the rice plant sprayed with a natural Guar gum-based film, which was incorporated with citral, an effective repellent for BPHs, RNA sequencing analysis showed that the relative mRNA level of an OBP coding gene named 797 was significantly decreased. 23 Compared with the naive control, the transcriptional level of some OBPs and CSPs of M. persicae was downregulated in the aphids continuously treated with EβF, and the aphids were less likely to be repelled by EβF. 24 Furthermore, it has been revealed that there were no significant differences in the populations of both aphids M. persicae and parasitized aphids between genetically modified wheat lines, which can stably produce EβF and untransformed control.…”
Section: Introductionmentioning
confidence: 99%